After the Carnation Revolution: Continuity and innovations in Portuguese odonomastics: The case of Aveiro - Raimundo, F.; Paris, A. (Memoria e Ricerca, 2025)
This study examines the sociopolitical dynamics of street naming and renaming in Aveiro, Portugal, following the 1974 coup which ended decades of dictatorship. Focusing on a non-capital city, this research contributes to the broader field of critical toponymy, which explores how public spaces and street names are politically and symbolically contested to reflect changes in regime, societal values, and historical narratives. Aveiro presents a unique case study due to its mixed political legacy of both alignment and opposition to the dictatorship. This paper analyzes the local administrative decisions of the first 20 years after the fall of the regime to understand the balance between recommemoration and decommemoration, the influence of political ideologies, and the role of community engagement in the toponymic changes. Utilizing municipal meeting minutes and a comprehensive database of local political figures, we show how, unlike Portugal’s generic approach to dealing with the past, street naming and renaming in Aveiro was an ongoing issue that lasted for many years. The initial attempt to conceal the local historical baggage of the party that controlled the local executive helps explain their cautious and often pragmatical approach.